Absorption and Excretion of Drugs. XX. Some Pharmacokinetic Aspects of Absorption and Excretion of Sulfonamides. (2). Absorption from Rat Small Intestine. - TAMOTSU KOIZUMI; Takaichi Arita; Kiichiro Kakemi (1964)
Rat small intestine was recirculated in situ with seventeen kinds of sulfonamide and five N4-acetyl derivatives, and absorption rate of the unionized drug was determined. The kinetical model proposed for the absorption of the drug from rat stomach also accounts for the absorption from rat small intestine, though the organic solvents that give suitable P are different.